The Rise and Spread of Behavioral Public Policy: An Opportunity for Critical Research and Self-Reflection - Holger Straßheim (International Review of Public Policy)
Some argue that the global rise of behavioral approaches challenges the rationalist tradition in public policy. Others fear that it could undermine deliberation and public reasoning. This paper focuses on the worldwide rise and spread of behavioral expertise and behavioral public policy. It provides a general insight in terms of the role of expertise, the science-policy nexus and the distribution of epistemic competences in public policy. Based on an extensive literature review, the emergence and consequences of behavioral-expert networks are assessed. It will be suggested that it is necessary to break free from the microfocus proposed by behavioral public policy and to pay more attention to the institutional and cultural constellations of knowledge- and decision-making in democracies.